ROLE OF 2% XYLOCAINE GEL IN MANAGING POSTOPERATIVE SORE THROAT IN GENERAL ANESTHESIA PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Background: Postoperative sore throat (POST) is a common complication following endotracheal intubation, causing significant patient discomfort.  Aim: This study evaluated the efficacy of 2% Xylocaine gel in reducing POST incidence and severity in patients undergoing general anesthesia.  Material and Methods: A prospective observational study was conducted on 84 patients (42 intervention , 42 control) at a tertiary care hospital. The intervention group received topical 2% Xylocaine gel prior to intubation, while the control group received standard care without anesthetic gel. POST incidence, severity (measured on a 10-point VAS), time of onset, and duration were assessed postoperatively. The Xylocaine group demonstrated significantly lower POST incidence (16.7% vs 52.4%, p